Strategi Pengembangan Kampung Adat Gebong Memarong (Kampung Adat Gebong Memarong) sebagai Destinasi Pariwisata Berbasis Masyarakat (CBT) Budaya di Kabupaten Bangka - Muhamad Galy Njoman Ari Pribowo; M Syafrizal Zian; Redi Alamsyah; Ganif Nur Annafi (UNIB Press, 2025)
Kampung Adat Gebong Memarong in Bangka Regency represents a cultural heritage of the Bangka Malay community and holds significant potential as a cultural-based tourism destination. However, tourism management in this area remains suboptimal due to low community involvement and the absence of an integrated development strategy. This study aims to formulate development strategies for Kampung Adat Gebong Memarong as a sustainable Community-Based Tourism (CBT) destination that empowers the local community. A qualitative approach with a case study design was employed, integrating the Participatory Rural Appraisal (PRA) method to explore community perspectives and aspirations in a participatory manner. Data were collected through in-depth interviews, participatory observations, focus group discussions (FGDs), and community mapping. The data were analyzed using descriptive SWOT analysis, along with Internal Factors Analysis Summary (IFAS) and External Factors Analysis Summary (EFAS). The findings reveal that community involvement is still symbolic and limited to ceremonial activities. However, the PRA method proved effective in fostering a sense of ownership and collective responsibility among the community. The SWOT analysis identified strengths in cultural authenticity and community solidarity, while weaknesses were found in human resource and institutional capacity. The conclusion of this study emphasizes the importance of strengthening community capacity, establishing multi-stakeholder partnerships, and integrating cultural narratives into digital promotion. This study contributes to the development of an inclusive and sustainable tourism model based on local wisdom.